2021
DOI: 10.1371/journal.pone.0251012
|View full text |Cite
|
Sign up to set email alerts
|

Vinpocetine alleviates lung inflammation via macrophage inflammatory protein-1β inhibition in an ovalbumin-induced allergic asthma model

Abstract: Asthma is a well-known bronchial disease that causes bronchial inflammation, narrowing of the bronchial tubes, and bronchial mucus secretion, leading to bronchial blockade. In this study, we investigated the association between phosphodiesterase (PDE), specifically PDE1, and asthma using 3-isobutyl-1-methylxanthine (IBMX; a non-specific PDE inhibitor) and vinpocetine (Vinp; a PDE1 inhibitor). Balb/c mice were randomized to five treatment groups: control, ovalbumin (OVA), OVA + IBMX, OVA + Vinp, and OVA + dexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Also, the results of IL-6 and TNF-α in the induced (BLM) group and the VCN-treated group were supported by the findings of Balaha et al in studying the protective effect of different doses of VCN in experimental pulmonary fibrosis in rats—the same observations regarding the oxidative markers (MDA, GSH, and SOD). In the context of IL-13, the results of the VCN-treated animals were supported by a previously published work investigating the anti-inflammatory effect of 10mg/kg of vinpocetine in a model of allergic asthma in mice 30 . In the context of altering the lung tissue expression of NF-κB and the inflammasome NLRP3, the results of the present work regarding the induced (BLM) group and the VCN-treated group were supported by a recently published study on the ameliorating effect of vincamine in pulmonary fibrosis in mice 67 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Also, the results of IL-6 and TNF-α in the induced (BLM) group and the VCN-treated group were supported by the findings of Balaha et al in studying the protective effect of different doses of VCN in experimental pulmonary fibrosis in rats—the same observations regarding the oxidative markers (MDA, GSH, and SOD). In the context of IL-13, the results of the VCN-treated animals were supported by a previously published work investigating the anti-inflammatory effect of 10mg/kg of vinpocetine in a model of allergic asthma in mice 30 . In the context of altering the lung tissue expression of NF-κB and the inflammasome NLRP3, the results of the present work regarding the induced (BLM) group and the VCN-treated group were supported by a recently published study on the ameliorating effect of vincamine in pulmonary fibrosis in mice 67 .…”
Section: Discussionsupporting
confidence: 60%
“…VCN has been mainly implicated in clinical and preclinical studies for the treatment of several Central Nervous System (CNS) disorders, such as cerebral ischemia, epilepsy, Alzheimer’s disease, and Parkinson’s disease 28 . In addition to this, VCN has been reported to show potential in the treatment of several inflammatory disorders, stress, glaucoma, and gastric disorders 29 ; in addition to these activities of VCN, a study published in 2021 by Choi et al about the anti-inflammatory effect of vinpocetine in a model of induced allergic asthma in mice made this agent interesting to investigate its activity in pulmonary fibrosis further 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with Dex (positive control) did not significantly suppress the numbers of lymphocytes, and monocytes when compared to the OVA group. Choi et al used a dose of 10 mg/kg of Dex every 2 days for 11 days to test the effects of Dex treatment on airway inflammation (Choi et al., 2021 ). They also used Dex as a positive control and showed that the numbers of eosinophils, macrophages, lymphocytes, and neutrophils in BALF decreased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…70 In another study, inhibition of tissue eosinophil infiltration as well as IL-13 and IgE levels was ameliorated by VNP in a mouse model of allergic inflammation. 119 Similarly, promising evidence has indicated that VNP might alleviate autoimmune ulcerative colitis in rats by hindering the extent of mucosal damage and the secretion of pro-inflammatory molecules. 48 Furthermore, VNP attenuates myelin expression and oligodendroglial cell maturation in individuals with autoimmune-related multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%